Impact of ZnO and Fe3O4 magnetic nanoscale on the methyl violet 2B removal efficiency of the activated carbon oak wood. (January 2022) - Foroutan, Rauf; Mohammadi, Reza; Ahmadi, Amir; Bikhabar, Gholamreza; Babaei, Fatemeh; Ramavandi, Bahman
Abstract: In the current study, activated carbon oak wood (ACOW600) and modified activated carbon using ZnO (ACOW600/ZnO) and Fe3 O4 (ACOW600/ZnO/Fe3 O4 ) nanoparticles were used to remove methyl violet 2B dye (MV2B) from aqueous solutions. ACOW was synthesized at different temperatures (300–700 °C), and then the maximum MV2B removal efficiency (92.76 %) was achieved using ACOW synthesized at 600 °C. The morphology and characteristics of ACOW600, ACOW600/ZnO, and ACOW600/ZnO/Fe3 O4 were studied using surface analyzes. According to the results, the adsorbents indicated a high ability to absorb MV2B from liquid solution, and their kinetic behavior follows a pseudo-second-order kinetic. In addition, the equilibrium study revealed that the MV2B uptake by the ACOW600/ZnO/Fe3 O4 magnetic nanocomposite followed the Freundlich model. In contrast, the Langmuir model described the MV2B adsorption process using ACOW600 and ACOW600/ZnO. The maximum adsorption capacity (qm ) of MV2B using ACOW600, ACOW600/ZnO, and ACOW600/ZnO/Fe3 O4 was determined 26.16 mg g −1, 37.05 mg g −1, and 48.59 mg g −1, respectively, indicating that modification of ACOW600 led to improve its performance in removing MV2B. The enthalpy (ΔH), entropy (ΔG), and Gibbs free energy (ΔS) parameters revealed that the decontamination of MV2B using the studied adsorbents was exothermic and spontaneous. Also, random interactions of MV2B molecules and adsorbent surfaces were reduced during the adsorption process. Textile wastewater was significantly treated by ACOW600, ACOW600/ZnO, and ACOW600/ZnO/Fe3 O4 adsorbents. The recycling of the adsorbents was demonstrated that the investigated adsorbents could be re-utilized many times in the MV2B removal process. Highlights: Activated carbon of oak was modified with iron oxides and zinc (ACOW600/ZnO/Fe3 O4 ). ACOW600/ZnO/Fe3 O4 magnetic composite was used to adsorb methyl violet 2B (MV2B). The BET value of ACOW600/ZnO/Fe3 O4 was 48 m 2 /g. The MV2B adsorption onto ACOW600/ZnO/Fe3 O4 followed the Freundlich model. The MV2B decontamination data was followed by pseudo second order model.